HUBUNGAN KECEPATAN DAN WAKTU REAKSI DENGAN HASIL LARI 100 METER PUTRA KELAS VII.1 SMPN 9 PEKANBARU - Amri, Fahmi; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based the observation and interview, the researcher found that the students’ 100 – metre sprint was below the average. The aim of the research was to get the correlation of speed and reaction time through 100 – metre sprint for 7.1 male students of SMP 9 Pekanbaru. The population of the research was the whole 7.1 male students and the amount was 16 students. The instruments were 50-yard test for speed, whole body reaction test for reaction time, and 100 – metre run for sprint. The data were analysed by using Product Moment Correlation. According to the correlation between speed and reaction time through 100 – metre sprint for SMP 9 Pekanbaru was concluded that from 14 students, there was a significant correlation between speed of 50-yard run and 100 – metre sprint with rhit 0.687 > rtab 0.553. Then, there was a significant correlation of the reaction time and 100 – meter sprint with rhit 0.579 > rtab 0.553 and there was a significat correlation of 50-yard run and the reaction time through 100 – meter sprint with rhit 0.841 > rtab 0.553.Keywords : Speed, reaction time, 100 – metre sprint